Об иранском подвиде горихвостки (Phoenicurus phoetiicurus samamisicus Hablizl) Северо-Западного Предкавказья - Очаповский, В.С. (Вестник зоологии, 1971)
Literature data available show that Phoenicurus pliocnicurus samamisicus H a b I i z I
inhabits the Caucasus, excluding the north foothills. However according to our data
the birds of this subspecies nest not only in the foothill zone but also on the plain,
occupying even the right bank of the Kuban (the flood forest in the Krasnodar environs).
The facts of nesting of the nominal and Iran subspecies in one and the same settlement
e. g. in the town of Goryachy Klyuch and village of Krasnaya Polyana are of greal
interest.
Some evidence is given concerning the quantity, periods of flying to and away and
nesting of the both subspecies.